Fertility Declines Near the End of the COVID-19 Pandemic: Evidence of the 2022 Birth Declines in Germany and Sweden - Martin Bujard; Gunnar Andersson (European Journal of Population, 2024)
Abstract Following the onset of the COVID-19 pandemic, many countries faced short-term fertility declines in 2020–2021, a development which did not materialize in the majority of German-speaking and Nordic countries. However, more recent birth statistics show a steep fertility decline in 2022. We aim to provide empirical evidence on the unexpected birth decline in 2022 in Germany and Sweden. We rely on monthly birth statistics and present seasonally adjusted monthly Total Fertility Rates (TFR) for Germany and Sweden. We relate the nine-month lagged fertility rates to contextual developments regarding COVID-19. The seasonally adjusted monthly TFR of Germany dropped from 1.5–1.6 in 2021 to 1.4 in early 2022 and again in autumn 2022, a decline of about 10% in several months. In Sweden, the corresponding TFR dropped from about 1.7 in 2021 to 1.5–1.6 in 2022, a decline of almost 10%. There is no association of the fertility trends with changes in unemployment, infection rates, or COVID-19 deaths, but a strong association with the onset of vaccination programmes and the weakening of pandemic-related restrictions. The fertility decline in 2022 in Germany and Sweden is remarkable. Common explanations of fertility change during the pandemic do not apply. The association between the onset of mass vaccinations and subsequent fertility decline indicates that women adjusted their behaviour to get vaccinated before becoming pregnant. Fertility decreased as societies were opening up with more normalized life conditions. We provide novel information on fertility declines and the COVID-19-fertility nexus during and in the immediate aftermath of the pandemic.
Keywords: 330; Fertility; Birth decline; COVID-19; Economic uncertainty; Vaccination; Oxford Stringency Index; Fertility plans